Biochemical markers in the management of suspected acute myocardial infarction in the emergency department. Issue 1 (1st January 2001) - Huggon, A M; Chambers, J; Nayeem, N; Tutt, P; Crook, M; Swaminathan, S
Abstract : Objectives —To compare cardiac troponin T, myoglobin, CK, CKMB activity, CKMB mass and the initial electrocardiogram in the early diagnosis of myocardial infarction in the emergency department. Methods —Biochemical markers were measured at presentation in patients with a possible diagnosis of acute myocardial infarction. Based on the clinical notes, patients were grouped as "definite myocardial infarction" (n = 50), "definite no myocardial infarction" (n = 81) and "uncertain" (n = 96). Sensitivity and specificity and positive and negative predictive values were calculated using the 131 patients with definitely present or absent myocardial infarction. Results —The initial electrocardiogram was more sensitive than any of the markers in the first six hours from symptom onset—sensitivity 74% (95%CI 61% to 88%). The positive predictive value of the initial electrocardiogram was 97% in the first six hours; the markers ranged from 47% to 67%. The negative predictive value of the initial electrocardiogram was 85% in the first six hours; the markers ranged from 61% to 70%. Four patients with non-diagnostic electrocardiograms presenting beyond six hours after pain onset had a myocardial infarct detected by at least three of the biochemical markers in each case. Conclusions —The electrocardiogram is of more diagnostic use than biochemical markers in the first six hours after the onset of pain, but biochemical markers give additional positive diagnostic information in patients presenting later than this. The negative predictive accuracy of biochemical markers is too low for a single sample to be useful for excluding myocardial infarction in the first six hours after onset of symptoms.